Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.1002/eap.2325
|View full text |Cite
|
Sign up to set email alerts
|

Land‐use drives the temporal stability and magnitude of soil microbial functions and modulates climate effects

Abstract: Land-use drives the temporal stability and magnitude of soil microbial functions and modulates climate effects. Ecological Applications

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
19
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 27 publications
(28 citation statements)
references
References 105 publications
(206 reference statements)
2
19
0
Order By: Relevance
“…Climate change, by means of increasing temperature and reduced precipitation in summer, can affect soil microbial communities, , but its effects on microbial colonization of plastics and plastic degradation rates have never been investigated. Recent biodegradable plastic microbiome studies in terrestrial environments hint that the microbiome assemblages of biobased and biodegradable plastics are comprised of diverse prokaryotes , and eukaryotes. However, most previous studies have focused either on specific species , or specific microbial kingdoms (Eubacteria or Fungi , ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Climate change, by means of increasing temperature and reduced precipitation in summer, can affect soil microbial communities, , but its effects on microbial colonization of plastics and plastic degradation rates have never been investigated. Recent biodegradable plastic microbiome studies in terrestrial environments hint that the microbiome assemblages of biobased and biodegradable plastics are comprised of diverse prokaryotes , and eukaryotes. However, most previous studies have focused either on specific species , or specific microbial kingdoms (Eubacteria or Fungi , ).…”
Section: Introductionmentioning
confidence: 99%
“…Herein, we present the first study on the decomposability of biobased and biodegradable PBSA in soil under natural ambient and predicted future climates in central Germany for the time between 2070 and 2100 (with an increase in mean daily temperatures by ∼0.55 °C, increase in minimum temperatures up to 1.14 °C in average, reduced precipitation by ∼20% in summer, and increased precipitation by ∼10% in spring and autumn) and the associated microbial communities using Illumina sequencing of amplified bacterial and archaeal 16S and fungal ITS2 regions. The climate manipulations implemented in this study have been reported to significantly affect soil microbes and plant litter decomposition. ,, The decomposition experiment was run for 328 days over four seasons. Specifically, we asked (i) whether PBSA decomposes under natural soil conditions, (ii) which microorganisms are associated with the degradation processes, and (iii) whether climate change (from now to the time between 2070 and 2100) will affect degradation rates and the composition of the associated microbial community.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, extensively used systems with high diversity promote soil microbial functions (Eisenhauer et al., 2013; Strecker et al., 2016; Thakur et al., 2015). Complimentary resource use, for example of plant rhizodeposition and temporal asynchrony of microbial activity, strengthen their resistance to environmental disturbances (Griffiths & Philippot, 2013; Kostin et al., 2021). Similarly, crop rotations promote microbial diversity by increasing the number of biological niches and temporal heterogeneity of plant inputs (Nelson & Spaner, 2010; Venter et al., 2016).…”
Section: Introductionmentioning
confidence: 99%
“…23 Climate change is known to be one of the most important factors that influence the soil microbiome and their interactions. 18,19 We set up our PBSA degradation field experiment under both ambient and future climate conditions to investigate the effects of future climate change on the interactions between fungi and N-fixing bacteria. We placed PBSA films (BioPBS FD92, PTT MCC Biochem Company Limited, Thailand; 35% of bio-based carbon derived from corn) in the form of a double-layer thin film with 50 μm thickness on top of the soil in conventional farming plots under both present and future climatic regimes.…”
Section: Methodsmentioning
confidence: 99%
“…Climate change has been reported to alter microbial interactions in soil, 18,19 with alterations in biodiversity and ecosystem productivity between ambient and predicted future climatic conditions. Our previous work on the degradation and microbiome of a bio-based and biodegradable plastic packaging and mulching film poly(butylene succinate- co -adipate) (PBSA) under ambient and future predicted climates for the years 2070–2100 showed that the molar and gravimetric masses of PBSA begin to drop at 180 days in soils after the blooming of N-fixing bacteria and of the main PBSA fungal colonizers ( Tetracladium spp.)…”
Section: Introductionmentioning
confidence: 99%